Synergistic Potential of Antimicrobial Combinations Against Methicillin-Resistant Staphylococcus aureus - Yu, Yang; Huang, Han-Liang; Ye, Xin-Qing; Cai, Da-Tong; Fang, Jin-Tao; Sun, Jian; Liao, Xiao-Ping; Liu, Ya-Hong (Frontiers in Microbiology, 2020)
The chemotherapeutic options for methicillin-resistant Staphylococcus aureus (MRSA) infections are limited. Due to the multiple resistant MRSA, therapeutic failure has occurred frequently even using antibiotics belong to different categories in clinical scenarios, very recently. This study aimed to investigate the interactions between 11 antibiotics representing different mechanisms of action against MRSA strains and provide therapeutic strategies for clinical infections. Susceptibilities for MRSA strains were determined by broth microdilution or agar dilution according to CLSI guideline. By grouping with each other, totally 55 combinations were evaluated. The potential synergism was detected through drug interaction assays and further investigated for the time-killing curves and in vivo neutropenic mouse infection model. Totally six combinations (vancomycin with rifampicin, vancomycin with oxacillin, levofloxacin with oxacillin, gentamycin with oxacillin, clindamycin with oxacillin and clindamycin with levofloxacin) showed synergistic activity against MRSA ATCC 43300 strain. However, antibacterial activity against clinical isolate #161402 was only observed when vancomycin combining with oxacillin or rifampicin in time-killing assays. Followed, therapeutic effectiveness of vancomycin/oxacillin and vancomycin/rifampicin was verified by in vivo mouse infection model inoculated with #161402. Further investigations on antimicrobial synergism of vancomycin combinations against 113 wild-type MRSA strains were evidenced by synergy of vancomycin plus oxacillin and vancomycin plus rifampicin were evidenced by combined antibiotic MICs and bacterial growth inhibition and in vitro dynamic killing profiles. In summary, vancomycin/rifampicin and vancomycin/oxacillin are the most potential combinations for clinical MRSA infection upon both in vitro and in vivo tests. Other synergetic combinations of levofloxacin/oxacillin, gentamycin/oxacillin, clindamycin/oxacillin, and clindamycin/fosfomycin are also selected but may need more assessment for further application.